TEACHING AND LEARNING ENGLISH AT HIGHER EDUCATIONAL INSTITUTIONS IN UKRAINE THROUGH PANDEMICS AND WARTIME - Руслана Вестерлунд; Oksana Chugai; Сергій Петренко; Ірина Зуєнок (Novìtnâ Osvìta, 2023)
The study aimed to analyse online English teaching and learning experience in higher education institutions in Ukraine through pandemics and wartime. To answer our research questions, we employed a mixed-method research design, which considered social, methodological and emotional aspects of education. We conducted quantitative research to collect data on the experience of Ukrainian university teachers of English (N=100) and students (N=277) related to the emergency caused by pandemics and wartime. The qualitative data sources included online interviews and written comments of the participants. The main findings were as follows: teachers experienced challenges during the COVID-19 pandemic such as lack of interaction with students, and unawareness of effective teaching methods in the digital environment. The wartime challenges included:  air raids and power outages and, consequently, disrupted  communication and isolation, stress and sense of insecurity, excessive workload, with  students experiencing technical issues, air raids and communication problems as well as large amount of homework, no access to the software, inconvenient schedule, and their own unwillingness. To solve the problems, teachers introduced an online synchronous mode during the COVID-19 pandemic, supported by blended and asynchronous modes which was a transformational period to teaching and learning English during wartime. The most common among the learning platforms and applications were Zoom and Google Classroom, as well as Moodle, MS Teams, YouTube, and Classtime, listed by both university teachers and students. Social networks such as Telegram, Viber, Facebook etc. were widely used too. To conclude, the COVID-19 pandemic caused Ukrainian teachers and students master new tools to use at online lessons of English, during wartime the demand  on already familiar tools, as well as the range of them, increased as they provided more  interaction. Considering emotional aspects, the study revealed disturbing data on teachers’ well-being: nearly 50% confessed that they were burned out and emotionally devastated, close to 40% were tired and pushed themselves to continue teaching.  Despite these challenges, the majority were able to find solutions in conflict situations with students and colleagues, two-thirds were sure that their work was even more important during the wartime and they found ways to provide emotional support to their students needed in the times of war.